Analysis Role of Digital Marketing and Self-Image Improving High School Students' Self-Presentation in Batam Using Instagram - Liegestu, Suryo Pramono; Muhammad, Ardiansyah; Eryc (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
With the rapid development of digital technology, Instagram serves as a critical platform for shaping self-image and promoting self-presentation among students. This study explores the influence of digital marketing and self-image on the self-presentation of high school students in Batam through Instagram, with Digital marketing and self-image serves as the independent variable and self-presentation as the dependant variable. Using a quantitative research method, data were collected from 353 respondents across 16 private high schools in Batam. The study finds that both digital marketing and self-image significantly affect students' self-presentation, with digital marketing enabling creative self-promotion and self-image enhancing confidence and personality expression. Key Instagram features like stories, highlights, reels, and posts are instrumental in fostering positive self-image and social interaction. Statistical analysis revealed that 22.8% of self-presentation is influenced by the studied variables, highlighting the role of external factors. This research underscores Instagram's role in inspiring fashion trends, promoting products, and cultivating a polished appearance, contributing to students' confidence and social perception. These findings have implications for understanding digital media's impact on youth behaviour and social identity